Sediments as a Source of Iron, Manganese, Cobalt and Nickel to Continental Shelf Waters (Louisiana, Gulf of Mexico) - Lenstra, Wytze K.; van Helmond, Niels A. G. M.; Żygadłowska, Olga M.; van Zummeren, Roosmarijn; Witbaard, Rob; Slomp, Caroline P. (Frontiers in Marine Science, 2022)
Continental shelf sediments are a key source of trace metals to the ocean. In this study, we investigate the impact of sedimentary processes on water column concentrations of iron (Fe), manganese (Mn), cobalt (Co) and nickel (Ni) at five stations on the Louisiana continental shelf and slope, Gulf of Mexico. The highest trace metal concentrations were observed close to the seafloor at the most nearshore shelf station (water depth of 16 m), with most of the metals present in particulate form. This enrichment in the bottom water is likely the combined effect of input of trace metals in suspended matter from the Mississippi/Atchafalaya Rivers and, for Mn, Co and Ni, benthic release from the shelf sediments. While particulate matter was the dominant carrier of Fe and Mn in bottom waters in the shelf and slope regions, Co and Ni were nearly exclusively present in dissolved form. Hence, lateral transport of Co and Ni in shelf waters is decoupled from that of Fe and Mn. Concentrations of particulate and dissolved trace metals in the water column generally decreased from the shelf to the slope, while those in the sediment increased. This suggests an increased retention of metals deposited on the sediment with distance from the coast, linked to the decrease in organic matter input and associated reductive sediment processes. The offshore decline in sediment trace metal mobilization is likely typical for river-dominated continental margins where most organic matter is deposited close to the coast.